PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN CUNGKRUNGAN, DESA BELUK, KECAMATAN BAYAT, KABUPATEN KLATEN, PROPINSI JAWA TENGAH - , LUQITA SYEIRA I ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project is based on the Job Training (PKL) who have previously completed. Therefore, this thesis describes the stage of making the situation map that contains the measurement method by using the basic framework of mapping and there are theories that explain the concept of measurement. The results of the measurement work is a map of the situation presented in 4 sheets of A1 size map with a scale of 1: 500 with UTM coordinate system (universal transverse Mercator). Fill contains detailed planimetric maps were displayed in the form of 2D images that are linked from the point - the point of measurement results and a detailed height contour lines are connected between points that have the same height with a certain interval.